Integrating Video Simulation into Hybrid Problem-Based Learning: A Strategy for Fostering Critical Thinking and Problem-Solving Abilities in Grade X Students Studying Basic Programming Algorithms - Suliantini, Deni Agustin; Masitoh, Siti; S Bachri, Bachtiar (Indonesia Emerging Literacy Education, 2024)
Objective: This study aims to determine the effectiveness of video simulation on hybrid problem-based Learning (PBL) in improving grade X students' critical thinking and problem-solving skills using primary programming algorithm material. Method: The research method used is quantitative, with a quasi-experimental research type and pretest-posttest control group design. This study involved 30 students in the control and 30 in the experimental classes. The research sample was selected using a purposive sampling technique with the criteria of grade X students studying basic programming algorithms. Data collection techniques used questionnaires or questionnaires from 2 research instruments: critical thinking and problem-solving abilities. Data analysis in this study used normality tests and homogeneity tests. Results: This study showed a significant increase in grade X students' critical thinking and problem-solving abilities in studying basic programming algorithms after video simulation integration in HPBL intervention. Novelty: The integration of video simulation in HPBL provides a concrete visual representation that helps students understand abstract concepts and apply theory in real situations, enriching the learning process of basic programming algorithms. Future research is expected to explore other learning methods to improve the effectiveness of hybrid problem-based learning so that students have a learning style in learning basic programming algorithms.